PENTINGNYA NILAI-NILAI PANCASILA DALAM MEMBENTUK KARAKTER SISWA KELAS IV SDN SOCAH 1 - Musdalifah Putri Sonia; Shintia Shepti Hariani; Apriyanur Rohim; Amma Azizah Munawarah; Rahma Maulidia Nur Fadilah; Widyo Trio Pangestu (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
This method uses descriptive qualitative research. The research subject was the result of direct observation of PKN teachers in grade IV at SDN Socah 1. The data collection methods used were observation, interviews and documentation. The results of research conducted by researchers regarding the importance of implementing Pancasila values ​​applied by teachers and fourth grade students at SDN Socah 1: 1) Belief in One Almighty God, In every religious lesson, SDN Socah 1 holds Duha prayers together, recites istighosah and after that prays. 2) Just and Civilized Humanity, students respect each other among friends and obey the teacher. 3) The Association of Indonesia, teachers and fourth grade students at SDN Socah 1 hold pickets so that an attitude of cooperation is always instilled. 4) Democracy Led by Wisdom Wisdom In Representative Deliberations, students have gotten used to deliberating with friends in solving problems. 5) Social Justice for All Indonesian People, In class IV SDN Socah 1 does not discriminate against anyone. Instilling Pancasila values ​​is very important in everyday life. Pancasila as the nation's view of life, which contains that Pancasila values ​​can be used as a guide or guide in regulating human behavior and attitudes. Thus it can be concluded that in this study students were able to apply the values ​​of the Pancasila precepts in everyday life to shape the character of elementary school children at SDN Socah 1.